Sex and rank in public service hierarchies: Rank distribution in Ghana’s health and security services - Ishmael D. Norman; Emmanuel Dodzi Kpeglo; Saralees Nadarajah (PLoS ONE, 2026)
This study analyses leadership patterns in Ghana’s health and security institutions since 1992, with a particular emphasis on the sex composition of senior positions in the Ghana Health Service, the Armed Forces, and the Police Service. A mixed-methods approach was employed, comprising a qualitative literature review, quantitative analysis of the Ghana Police Service rank hierarchies, assessment of the Military Occupational Physical Assessment Test in relation to Military Occupational Specialties, and content analysis of relevant sections of the Affirmative Action Act (2024). In 2025, women represented 39% of doctors (5,068/12,900), 30% of police officers (12,945/43,968), and 15% of soldiers (2,400/16,000) in Ghana. Leadership in the Ghana Armed Forces remained male-dominated, with fewer than five female Generals among 115 in the forces and only one female Inspector-General of Police since 1992. Statistical analysis of police rank distribution showed a significant association between sex and rank (χ², p < 0.05), indicating persistent disparities in career progression. Findings highlight systemic institutional barriers affecting women’s advancement in Ghana’s health and security sectors. Targeted institutional reforms aligned with the requirements and merit-based principles of the Affirmative Action Act (2024) are necessary to address the disparities and strengthen equitable representation.